Potential of garlic (Allium sativum) essence in changing blood lipid profile of hypertension patients with hypercholesterolemia - Hadi Hadi; Suharyo Hadisaputro; Djamaluddin Ramlan (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: As like hypertension, hypercholesterolemia is a major risk factor for cardiovascular disease and hypertension and its complications are one of the highest causes of death in the world.Aims: This study aims to determine the potential of garlic essence (Allium sativum) mixed with honey in changing blood pressure and lipid profile of blood in the hypertension patients with hypercholesterolemia, and to compare the effectiveness with those who received Simvastatin, the most preferred pharmacological treatment of hyperlipidemia.Methods: This research is a quasy experiment study with a Nonequivalent control group design. There were 22 hypercholesterolemia outpatients purposively selected from local health centers. The respondents were then divided equally to (a) a control group where the patients were provided with generic Simvastatin 10 mg single dose taken once in the afternoon, and (b) an intervention group where the respondents received a non-pharmacological supplement of garlic essence in 2 grams honey. The blood pressure and the blood lipid profile were examined before (Pretest) and at the Day 22 after the treatment (Posttest). The collected data was then analyzed using a T-test to define the significant mean difference between two groups, and a Cohen’s effect was measured to interpret the size of changes.Results: Either the additions of Simvastatin or the provision of garlic essence mixed with honey decreased the blood pressure (systole and diastole) and the cholesterol, triglyceride, and LDL cholesterol, but increased the HDL cholesterol. While significant difference was observed for all parameters at the intervention group, the improvement at the control group for triglyceride was not significant (p value = 0.041). Overall, by the Cohen's effect size effect, we can interpret that the changes was moderate for diastole and systole blood pressure, and also triglyceride and DLD-cholesterol; however the effect size was low for Cholesterol and HDL-cholesterol. Conclusion: The findings show the importance of the garlic essence mixed with honey to be offered as a nutritional supplement for hypertensive patients with hypercholesterolemia. Keywords: Garlic (Allium sativum) essence, Simvastatin, Hypertension, Hypercholesterolemia, Blood pressure, Blood lipid profile.